Analysis of Influencer Marketing Campaigns in Digital Marketing on the TikTok Platform - Dhevyta Nabila Rahman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to identify the factors influencing the success of the campaign for the brand “Kata Oma” conducted by Dina Amrianti on the TikTok platform. This research employs the TEARS model (Trustworthiness, Expertise, Attractiveness, Respect, and Similarity) proposed by Shimp in 2014, which is a framework used to understand the factors affecting the success of influencer marketing strategies. The research approach used in this study is a qualitative approach with a descriptive method. The number of informants involved in this study is thirteen, consisting of two people from the “Kata Oma” brand and eleven followers of the @lordjajanofficial account. Data collection techniques were conducted through in-depth interviews with the informants. The data analysis technique used in this study is the interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing or verification. The research findings indicate that the influencer marketing campaign for the “Kata Oma” brand conducted by Dina Amrianti on the TikTok platform has been successful using the TEARS model. Interview data from the thirteen key informants show that Dina Amrianti's followers consider trust and honesty in her reviews of the “Kata Oma” spicy balado variant to be key to the effectiveness of the influencer marketing campaign. Dina successfully leveraged her knowledge and expertise with a cheerful style that attracted the audience's interest in trying the “Kata Oma” product, although there is an expectation for more in-depth details from the audience.